STRATEGI PENGEMBANGAN AGRIBISNIS STROBERI PADA CV. BUMI AGRO TECHNOLOGY, JAWA BARAT - Mikha Gracina Devonian Silaban; Lucyana Trimo (Universitas Galuh Ciamis, 2021)
CV. Bumi Agro Technology is a company engaged in the production of strawberry’s plant seeds and fruis which has a good reputation in West Java. However, the production of strawberry’s seeds and fruits in CV. Bumi Agro Technology is fluctuating so it can be said that the strawberry farming is still not being carried out optimally. Therefore, CV. Bumi Agro Technology needs to develop strawberry agribusiness by first identifying the strengths, weaknesses, opportunities and threats faced by the company. This study aims to determine the internal and external factors in the company and obtaine the viable strawberry agribusiness development strategies to optimize its business. The design in this study used a qualitative design with a case study research technique. Data collection methods used such as interview, observation and literature study. In determining the development strategy, it is divided into three stages. The first stage is input stage which uses the IFE and EFE matrix. The matching stage uses IE matrix and SWOT matrix. The last stage is the decision stage using the QSPM matrix. From the results of the SWOT analysis, it was obtained eight alternative strategies which were further analyzed using QSPM with the following priority strategies: 1) Maintaining product quality, (2) Increasing job training, (3) Increasing promotion, (4) Improving financial systems, (5) Creating new strawberry varieties, (6) Utilizing empty land in production areas, (7) Maintaining and improving service quality to consumers and (8) Developing partnerships between companies and consumers and also farmers.